Telomere shortening reduces regenerative capacity after acute kidney injury - Westhoff, Jens; Schildhorn, Carolin; Jacobi, Christoph; Hömme, Meike; Hartner, Andrea; Braun, Heidi M.; Kryzer, Christine; Wang, Chunfang; von Zglinicki, Thomas; Kränzlin, Bettina; Gretz, Norbert; Melk, Anette (Journal of the American Society of Nephrology, 2010)
Telomeres of most somatic cells progressively shorten, compromising the regenerative capacity of human tissues during aging and chronic diseases and after acute injury. Whether telomere shortening reduces renal regeneration after acute injury is unknown. Here, renal ischemia-reperfusion injury led to greater impairment of renal function and increased acute and chronic histopathologic damage in fourth-generation telomerase-deficient mice compared with both wild-type and first-generation telomerase-deficient mice. Critically short telomeres, increased expression of the cell-cycle inhibitor p21, and more apoptotic renal cells accompanied the pronounced damage in fourth-generation telomerase-deficient mice. These mice also demonstrated significantly reduced proliferative capacity in tubular, glomerular, and interstitial cells. These data suggest that critical telomere shortening in the kidney leads to increased senescence and apoptosis, thereby limiting regenerative capacity in response to injury.
Gesehen am 29.11.2023